Supernatural Snag and Killer Whale Mortuary - Unknown (1924)
On the post was a supernatural snag in human form at the top and a killer whale at the base that is being obscured by vegetation. The front plaque of the mortuary was plain, with the high dorsal fin of the killer whale projecting above the plaque.